Incidence and distribution of cassava diseases and pests in the Democratic Republic of Congo - Tata-Hangy, K.W.; Legg, James P.; Hanna, R.; Toko, M.; Lema, K.M.; Dixon, A.; Mahungu, N.M. (International Society for Tropical Root Crops, 2007)
A countrywide survey on cassava constraints in D.R. Congo was initiated in 2002 and completed in 2004 with the aim of assessing the health status of cassava in various agro-ecological zones of the 11 provinces of the country. The survey permitted to update the list of diseases and pests that continue to threaten cassava production in the country. Among the diseases, cassava mosaic virus disease (CMD) was observed to be the most damaging and widely distributed. The incidence was high in all the provinces surveyed averaging 85%. Strains of the viruses responsible of the disease were identified, and included the African Cassava Mosaic Virus (ACMV), and the Uganda variant of East African Cassava Mosaic Virus (EACMV-Ug). Cassava bacterial blight (CBB) and cassava anthracnose disease (CAD) were also observed, however severe incidence and damage were limited to some provinces. The root rot diseases were not frequently observed in the field during the survey. However, a questionnaire was used, farmers in Bandundu, Kivu and Province Orientale complained that root rots were one of the major damaging constraints of cassava, particularly when cassava is harvested late (eg above 18 months after planting). Cassava brown streak virus disease (CBSD) was not observed in much of the areas sampled except in Kinshasa and Bas-Congo provinces where the incidences were rather low. Africa, cassava green mite (CGM) was the most widespread in DRC. However, its incidence and severity were low in the provinces where the exotic natural enemy predatory mite Typhlodromalus aripo had been introduced and is established. Cassava mealybug (CM) was also found in few locations in a limited number of provinces e.g Kinshasa, Bandundu, Kasai Oriental and Kasai Occidental. The low spread and incidence of CM recorded during the survey confirms observations that CM has effectively been controlled by the parasitic wasp Apoanagyrus lopezi De Santis that was released throughout the country in the 1980s. The resurgence of the pest in the few provinces cited above can therefore be attributed to several factors such as the susceptibility of cassava variety (induced by the severe mosaic disease), poor crop management and low soil fertility. Arecently reported pest, the African root and tuber scales (ARTS), whose distribution is limited only to forest zones was observed in Bas-Congo, Province Orientale and Nord-Kivu where the incidence was generally high. Two arthropod species, the Thrips and termites, known in the recent past to be secondary pests of cassava in DRC are now showing high incidence and alarming damages. The whitefly Bemisia tabaci, traditionally known as vector of the virus that cause the cassava mosaic disease (CMD) was observed in very high number inducing honeydew on the cassava leaves.